Speak out! - UNICEF (Nairobi, Kenya : UNICEF Eastern & Southern Africa Regional Office, 2004)
Sexual violence has been recognised as a major problem in and school s in sub-Saharan Africa. Evidence shows that it is a major barrier to a ccelerating progress in girls' education. This documentary eloquently c aptures the voices of young people in Swaziland speaking out against se xual abuse and highlights their efforts to combat gender-based violence . It is a useful tool for facilitating dialogue and action against sexu al violence with communities and schools.
For every child Health, Education, Equality, Protection advance huma nity.
Keywords: Sex crimes -- Swaziland